Figurative elements in Jota Sara’s book My Folklore - Cruz, Clériston Jesus da; Bitencourt, Denise Silva (Estudos Semióticos, 2016)
In this study, some excerpts from My Folklore (1957), by José Aras, the Jota Sara pseudonym, areseen in the light of Greimas semiotics, with regard especially to the perception of the themes and figures,elements present in the Semantics Discourse the Generative Sense course. Present the semiotic concepts ofisotopy and figuration. Thus, the aim is to list the figurative investments, revealing therefore the place ofideology in the speech, i.e. the conselheirista vision. Even in this quest, the religious references are highlightedthat the text in question, became a semantic resource construction of the effects of truth. For this purpose,extracts from hand launches the following authors: Belém (1940), Silva (s/d), Cunegundes (1897), Calasans(1984), as well as some excerpts from Santos (1897), The Popular Catholic Encyclopedia and other works ofJosé Aras (1963, 2003 and 2009). Moreover, Fiorin (2006), Barros (2005), Oliver (2013), based ongreimasianos studies provide very important subsidies for effective analysis.